1998
DOI: 10.1159/000024950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibodies to the Epstein-Barr Virus Immediate Early Gene Product ZEBRA by a New Enzyme-Linked Immunosorbent Assay

Abstract: For the serodiagnosis of Epstein-Barr virus (EBV) infections, we have developed a new enzyme-linked immunosorbent assay (ELISA) for antibodies to the ZEBRA product of EBV immediate early gene BZLF1. ZEBRA protein fused with glutathione-S-transferase (GST) was expressed in Escherichia coli and purified by affinity chromatography with glutathione-Sepharose 4B. An ELISA sandwich capture system was constructed with the GST-ZEBRA immobilized on plastic microtiter plates which had been coated with a mouse monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…In effect, 42 of 47 sera (89.3%) displaying a antibody profile typical of an acute primary EBV infection (VCA IgG ϩ or VCA IgG Ϫ , VCA IgM ϩ , and EBNA-1 IgG Ϫ ) gave a positive result in the IMFA. This figure is in contrast with that (14%) previously reported by another group (18). The most likely explanation for this discrepancy is the different natures of both the antigens and the immunoassay formats employed (a prokaryotic recombinant ZEBRA protein and a sandwich capture enzyme-linked immunosorbent assay were used in the abovementioned study, whereas a combination of immunogenic ZEBRA-derived synthetic peptides were employed in the evaluated IMFA in this study).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In effect, 42 of 47 sera (89.3%) displaying a antibody profile typical of an acute primary EBV infection (VCA IgG ϩ or VCA IgG Ϫ , VCA IgM ϩ , and EBNA-1 IgG Ϫ ) gave a positive result in the IMFA. This figure is in contrast with that (14%) previously reported by another group (18). The most likely explanation for this discrepancy is the different natures of both the antigens and the immunoassay formats employed (a prokaryotic recombinant ZEBRA protein and a sandwich capture enzyme-linked immunosorbent assay were used in the abovementioned study, whereas a combination of immunogenic ZEBRA-derived synthetic peptides were employed in the evaluated IMFA in this study).…”
Section: Discussioncontrasting
confidence: 77%
“…To our knowledge, there are no published data in relation to the clinical value of assessing the presence of IgMs to ZEBRA for the diagnosis of EBV IM except for a study evaluating the performance of a capture enzyme-linked immunosorbent assay that detects antibodies to a recombinant ZEBRA protein (18). The ZEBRA immunofiltration test was found to be highly sensitive (92.5%) and specific (97.3%) for the diagnosis of EBV IM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As described above, the ZEBRA antibody is a sensitive and specific serological marker for detecting EBV-associated disease because it is rare among normal samples (6,27). High levels of anti-ZEBRA antibody could be used not only as a biological marker in the follow-up of NPC and non-Hodgkin's lymphoma patients but also for the prognosis of EBV infectious diseases (22)(23)(24). It has been reported that IgA antibodies could more effectively indicate the risk of NPC (2).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, epitopes on the protein are presented to antibodies in the least obstructed and most desirable way. Several attempts have been made to immobilize pure GST to the bottom of the microwell (Cartwright et al, 1995), covalently link GST to another protein such as haemoglobin (Murray et al, 1998) or casein (Sehr et al, 2001) or to directly bind mammalian antibodies against GST (monoclonal or polyclonal) to the bottom of the plate (Kilty et al, 1998;Yamauchi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%